Antioxidant Capacity and Polyphenolic Composition as Quality Indicators for Aqueous Infusions of Salvia officinalis L. (sage tea) - Walch, Stephan G.; Ngaba Tinzoh, Laura; Zimmermann, Benno F.; Stühlinger, Wolf; Lachenmeier, Dirk W. (Frontiers in Pharmacology, 2011)
Sage (Salvia officinalis L.) is used as an herbal medicinal product, with the most typical form of application as infusion with boiling water (sage tea). The well-established traditional uses include symptomatic treatment of mild dyspeptic complaints, the treatment of inflammations in the mouth and the throat, and relief of excessive sweating and relief of minor skin inflammations. In this study, sage teas prepared from commercially available products were chemically analysed for polyphenolic content using liquid chromatography, for antioxidant potential using the oxygen radical absorbance capacity (ORAC) method, and for the Folin-Ciocalteu (FC) index. The sage teas showed a high variation for all parameters studied (up to 20-fold differences for rosmarinic acid). Univariate and multivariate analyses showed that the antioxidant potential, which varied between 0.4 and 1.8 mmol trolox equivalents/100 mL, was highly dependent on rosmarinic acid and its derivatives. The FC index also showed a high correlation to these polyphenols, and could therefore be used as a screening parameter for sage tea quality. The considerable differences in polyphenolic composition and antioxidant capacity between the brands lead to a demand for quality standardisation, especially if these sage teas are to be used for therapeutic purposes. Further research also appears to be necessary to characterise the dose-benefit relationship, as sage may also contain a constituent (thujone) with potentially adverse effects.